2012
DOI: 10.4067/s0716-97602012000400008
|View full text |Cite
|
Sign up to set email alerts
|

Biological screening of selected flora of Pakistan

Abstract: Methanolic extracts of diff erent parts of fi ve medicinal plants, Ferula assafoetida L. resin, Grewia asiatica L. leaves, Ipomoea hederacea Jacq. seeds, Lepidium sativum L. seeds and Terminalia chebula Retz. fruits were tested in vitro for their cytotoxic, phytotoxic, insecticidal, nematicidal and anthelmintic activities. Ipomoea hederacea showed very signifi cant phytotoxic and cytotoxic activity, with 100% inhibition of Lemna minor growth and 100% death of Artemia salina at concentrations of 1000 and 100 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The cytotoxicity of plant extracts with LC 50 value ≤ 20 µg/mL was regarded as a possible cytotoxic plant extract [63]. The results indicated that most plant extracts had low cytotoxicities with considerably high LC 50 value ≥ 100 µg/mL, excluding S. tuberculate (LC 50 = 25.9 µg/mL), D. odorifera (LC 50 = 44.1 µg/mL), I. japonica (LC 50 = 54.1 µg/mL), R. chinensis (LC 50 = 77.6 µg/mL), and Q. infectoria (LC 50 = 91.6 µg/mL), supporting by previous studies that also found a weak cytotoxicity of T. chebula [64,65], S. suberectus [66], Q. infectoria [67,68] and O. indicum [37]. However, it is necessary to test the toxicity by in vivo studies, since in vitro cellular toxicity might provoke different consequences in animals associated with gut interactions and bioavailability of the extracts [18].…”
Section: Cytotoxicity and Safety Of The Tcmp Extractssupporting
confidence: 82%
“…The cytotoxicity of plant extracts with LC 50 value ≤ 20 µg/mL was regarded as a possible cytotoxic plant extract [63]. The results indicated that most plant extracts had low cytotoxicities with considerably high LC 50 value ≥ 100 µg/mL, excluding S. tuberculate (LC 50 = 25.9 µg/mL), D. odorifera (LC 50 = 44.1 µg/mL), I. japonica (LC 50 = 54.1 µg/mL), R. chinensis (LC 50 = 77.6 µg/mL), and Q. infectoria (LC 50 = 91.6 µg/mL), supporting by previous studies that also found a weak cytotoxicity of T. chebula [64,65], S. suberectus [66], Q. infectoria [67,68] and O. indicum [37]. However, it is necessary to test the toxicity by in vivo studies, since in vitro cellular toxicity might provoke different consequences in animals associated with gut interactions and bioavailability of the extracts [18].…”
Section: Cytotoxicity and Safety Of The Tcmp Extractssupporting
confidence: 82%
“…Insects control relies heavily on the use of synthetic insecticides; however, their widespread use has led to various problems such as the development of insect strains resistant to insecticides (Zia-Ul-Haq et al, 2012). The plant produces various secondary metabolites for defense purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Monoterpenes, sesquiterpenes lactones and triterpenes are some of the secondary metabolites of various plants that possess insecticidal activity (Barney et al, 2005;Cespedes et al, 2015;Sosa and Tonn, 2008). Crude extracts of Lepidium sativum and Ipomoea hederacea showed the highest insecticidal activity against all three insects as compare to Sterculia diversifolia (Zia-Ul-Haq et al, 2012). Sterculia diversifolia stem bark, n-hexane fraction showed mild to moderate activity against all insects, while the MESD and n-hexane fraction of leaf showed highest activity against Rhyzopertha dominica and Callosobruchus analis respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these plants have accidentally caught the attention of farmers and the general public to control bacteria [2], viruses and insects [3]. These simple observations are considered as initial and preliminary indications that have led a large number of researchers, since the beginning of the twentieth century, to the feasibility of applying them in a deliberate manner against insects [4,5,6,7]. Lepidium sativum: Cruciferae is a popular medicine plant that is widespread in different regions [1,8].…”
Section: Introductionmentioning
confidence: 99%